Viewing violence: how media violence affects your child's and adolescent's development - Levine, Madeline (Doubleday, 1996)
Psychologist and mother Madeline Levine looks at the history of television and movie violence in the United States. She translates into everyday language the results of over four decades of research on the effects of media violence - research that up until now has been inaccessible to most parents. Using a "developmental approach," Dr. Levine helps parents understand that children at different ages think about, understand, and experience the world in very different ways. An appreciation of these differences in how children "see" things is critical if parents are to make wise choices about what is appropriate and what is potentially harmful to their children. Using research findings, common sense, and personal experience, Dr. Levine demonstrates that violence is not generic - and neither are children: the movie that may be instructive and appropriate for an eleven-year-old may be traumatic and overwhelming for a seven-year-old